2023
DOI: 10.1101/2023.02.09.527916
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disrupted sleep in dystonia depends on cerebellar function but not motor symptoms in mice

Abstract: Although dystonia is the third most common movement disorder, patients often also experience debilitating nonmotor defects including impaired sleep. The cerebellum is a central component of a ″dystonia network″ that plays various roles in sleep regulation. Importantly, the primary driver of sleep impairments in dystonia remains poorly understood. The cerebellum, along with other nodes in the motor circuit, could disrupt sleep. However, it is unclear how the cerebellum might alter sleep and mobility. To disenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 76 publications
11
12
0
Order By: Relevance
“…Consequently, a primary objective of our study was to investigate how cerebellar nuclei DBS might improve overall sleep quality in Ptf1a Cre ;Vglut2 fx/fx and Pdx1 Cre ;Vglut2 fx/fx mice. At baseline (Pre-DBS), representative hypnograms indicate that both Ptf1a Cre ;Vglut2 fx/fx and Pdx1 Cre ;Vglut2 fx/fx mice display overall greater time awake and less time asleep relative to controls, similar to our previous findings 16 . Remarkably, during DBS, the proportions of wakefulness and sleep time began to converge across all mouse groups, demonstrating a rectification of sleep dysfunction.…”
Section: Targeting the Cerebellum With Dbs Does Not Impair The Acquis...supporting
confidence: 86%
See 3 more Smart Citations
“…Consequently, a primary objective of our study was to investigate how cerebellar nuclei DBS might improve overall sleep quality in Ptf1a Cre ;Vglut2 fx/fx and Pdx1 Cre ;Vglut2 fx/fx mice. At baseline (Pre-DBS), representative hypnograms indicate that both Ptf1a Cre ;Vglut2 fx/fx and Pdx1 Cre ;Vglut2 fx/fx mice display overall greater time awake and less time asleep relative to controls, similar to our previous findings 16 . Remarkably, during DBS, the proportions of wakefulness and sleep time began to converge across all mouse groups, demonstrating a rectification of sleep dysfunction.…”
Section: Targeting the Cerebellum With Dbs Does Not Impair The Acquis...supporting
confidence: 86%
“…Echoing our previous research 16 , these results point to cerebellar dysfunction, rather than motor impairment alone, as the likely origin of sleep deficits, given that both mutant mouse types, regardless of their motor condition, showed comparable sleep improvements during DBS.…”
Section: Targeting the Cerebellum With Dbs Does Not Impair The Acquis...supporting
confidence: 70%
See 2 more Smart Citations
“…Next, we set out to identify whether the dystonia signature was shared across mice with overt dystonic phenotypes. We included two dystonia models in our analyses; Pdx1 Cre ;Vglut2 fl/fl mice exhibit mild dystonic symptoms only in response to a stressful event (32,33) (Figure 3A-B), whereas mice that receive ouabain applied to the surface of the cerebellum exhibit continuous severe dystonic features (34,35) (Figure 3A-B). We found that the proportion of neurons that exhibited the control signature was greater in Pdx1 Cre ;Vglut2 fl/fl mice than in ouabain infusion mice (7/23 vs. 13/21, z=-2.094, p=0.0366) (Figure 3C).…”
Section: Dystonic Spike Train Signatures Are Shared Across Etiologica...mentioning
confidence: 99%